Annual ovarian cycle of fresh water catfish Ompok bimaculatus (Bloch, 1794) from Gomati river, India - MISHRA, ABHA; RAWAT, ANURAG (The Indian Journal of Animal Sciences, 2018)
The present study examined the gonadosomatic index (GSI), oocyte diameter (OD), ovarian morphology and histology of freshwater butter catfish Ompok bimaculatus from Gomati river, India. For the annual cycle study, monthly samples were collected from the Gomati river. The GSI increased with the progressively maturation of gonad. It increased significantly in July (4.98±0.047) and it reached its peak point in the month of August (5.37±0.037) and lowest value was observed in October month (0.64±0.019). The OD varied from 0.052±0.005 to 0.84±0.024; the maximum OD was observed in August month and lowest was observed in September month. It showed a significant relationship with GSI. Histological studies of ovary of O. bimaculatus revealed eight stages in oocyte development (oogonia, chromatin nucleolus, early perinucleolus, late perinucleolus, yolk vesicle, vitellogenesis, vitellogenic and post ovulatory follicles). The month wise studies of different parameters helped in confirming annual cycle as; resting phase (November-February), preparatory phase (March-April), pre-spawning phase (May- June), spawning phase (July-August) and post-spawning phase (September-October). These observations are important for a better understanding of reproductive biology of this fish in northern region to adopt breeding practices of female Ompok bimaculatus.